Zapatista Education as a Basis for Autonomy in South-Eastern Mexico - Bruno Baronnet (Universidade Federal do Rio Grande do Sul, 2015)
From the perspective of the Mayan Zapatistas in Chiapas, the subjects promoting education are all the members of the community, who often participate directly through a renewed system of community labours and assemblies, in building schools, choosing autonomous education promoters and in maintaining and training them. With emancipatory goals based on praxis, classroom content is proposed and discussed by members of families, educators and community authorities. Despite difficulties in everyday life, the political autonomy in education guarantees the specific organizational identity of indigenous communities in defining their educational activities.